Base editor correction of COL7A1 in recessive dystrophic epidermolysis bullosa patient-derived fibroblasts and iPSCs - Osborn, Mark J. (J Invest Dermatol, 2019)
Genome editing represents a promising strategy for therapeutic correction of COL7A1 mutations that cause recessive dystrophic epidermolysis bullosa (RDEB). DNA cleavage followed by homology-directed repair (HDR) using an exogenous template has previously been used to correct COL7A1 mutations. HDR rates can be modest and the double-strand DNA breaks that initiate HDR commonly result in accompanying undesired insertions and deletions (indels). To overcome these limitations, we applied an A•T→G•C adenine base editor (ABE) to correct two different COL7A1 mutations in primary fibroblasts derived from RDEB patients. ABE enabled higher COL7A1 correction efficiencies than previously reported HDR efforts. Moreover, ABE obviated the need for a repair template and minimal indels or editing at off-target sites was detected. Base editing restored endogenous type VII collagen expression and function in vitro. We also treated induced pluripotent stem cells (iPSCs) derived from RDEB fibroblasts with ABE. The edited iPSCs were differentiated into mesenchymal stromal cells, a cell population with therapeutic potential for RDEB. In a mouse teratoma model, skin derived from ABE-treated iPSCs showed proper deposition of C7 at the dermal-epidermal junction in vivo. These demonstrate that base editing provides an efficient and precise genome editing method for autologous cell engineering for RDEB.